Leishmania infantum Parasites Subvert the Host Inflammatory Response through the Adenosine A2A Receptor to Promote the Establishment of Infection - Lima, Mikhael H. F.; Sacramento, Lais A.; Quirino, Gustavo F. S.; Ferreira, Marcela D.; Benevides, Luciana; Santana, Alynne K. M.; Cunha, Fernando Q.; Almeida, Roque P.; Silva, João S.; Carregaro, Vanessa (Frontiers in Immunology, 2017)
Adenosine is an endogenously released purine nucleoside that signals through four widely expressed G protein-coupled receptors: A1, A2A, A2B, and A3. Of these, A2AR is recognized as mediating major adenosine anti-inflammatory activity. During cutaneous leishmaniasis, adenosine induces immunosuppression, which promotes the establishment of infection. Herein, we demonstrated that A2AR signaling is exploited by Leishmania infantum parasites, the etiologic agent that causes Visceral Leishmaniasis, to successfully colonize the vertebrate host. A2AR gene-deleted mice exhibited a well-developed cellular reaction with a strong Th1 immune response in the parasitized organs. An intense infiltration of activated neutrophils into the disease-target organs was observed in A2AR−/− mice. These cells were characterized by high expression of CXCR2 and CD69 on their cell surfaces and increased cxcl1 expression. Interestingly, this phenotype was mediated by IFN-γ on the basis that a neutralizing antibody specific to this cytokine prevented neutrophilic influx into parasitized organs. In evaluating the immunosuppressive effects, we identified a decreased number of CD4+ FOXP3+ T cells and reduced il10 expression in A2AR−/− infected mice. During ex vivo cell culture, A2AR−/− splenocytes produced smaller amounts of IL-10. In conclusion, we demonstrated that the A2AR signaling pathway is detrimental to development of Th1-type adaptive immunity and that this pathway could be associated with the regulatory process. In particular, it promotes parasite surveillance.